The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5603/rpor.a2022.0057
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional (3D) anatomic location, extension, and timing of severe osteoradionecrosis of the mandible

Abstract: Background:The purpose of this study was to describe the topography, extension (volume), and timing of severe osteoradionecrosis (ORN) that required mandible resection in patients previously treated for head and neck cancer at a high-volume Veterans Affairs Medical Center. Materials and methods:The records from a reference hyperbaric oxygen clinic were retrospectively analyzed (n = 50, 2018-2021). Inclusion criteria were: I) severe ORN defined as progressive ORN that required resection; II) pathologic confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…ORN can develop from months to years after RT [3] with Sapienza et al . [14] reporting that ORN can develop even 5–10 years post-RT. Multiple studies reported post-RT incidence of ORN was higher in males than females [3,5,11,13,15] because incidence of HNC is higher in males and behavioural factors linked to ORN development and HNC risk being more common in males [16,17].…”
Section: Literature Reviewedmentioning
confidence: 99%
See 1 more Smart Citation
“…ORN can develop from months to years after RT [3] with Sapienza et al . [14] reporting that ORN can develop even 5–10 years post-RT. Multiple studies reported post-RT incidence of ORN was higher in males than females [3,5,11,13,15] because incidence of HNC is higher in males and behavioural factors linked to ORN development and HNC risk being more common in males [16,17].…”
Section: Literature Reviewedmentioning
confidence: 99%
“…Patients whose primary tumour was in the oropharynx had the highest incidence of developing ORN (6%) [14] and oral cavity was reported to be the most common primary tumour site (45%) with squamous cell carcinomas accounted for 77.5% of the patients [13,14].…”
Section: Literature Reviewedmentioning
confidence: 99%